Investigation of Energy Losses Induced by Non-Uniform Inflow in a Coastal Axial-Flow Pump - Fan Meng; Yanjun Li; Jia Chen (Journal of Marine Science and Engineering, 2022)
A non-uniform velocity profile occurs at the inlet of a coastal axial-flow pump which is placed downstream of the forebay with side-intake. As a result, the actual efficiency and head of the pump is dissimilar to the design parameters, and the lack of the theoretical investigation on the relationship between inflow distortion and energy losses restricts the application of the coastal axial-flow pump in the drainage project. In this paper, the unsteady numerical simulation and entropy production theory are employed to obtain the internal flow structure and quantify energy losses, respectively, with three inflow deflection angles (<semantics>θ</semantics> = 0°, 15°, or 30°). It is reported that the best efficiency point (BEP) shifts to large flow rate with <semantics>θ</semantics> increasing, due to the decline of the velocity component in axial direction at the impeller inlet. Therefore, the total entropy production (TEP) of the coastal axial-flow pump rises with <semantics>θ</semantics> increasing under small flow rates, but it decreases with <semantics>θ</semantics> increasing under large flow rates. The high total entropy production rate (TEPR) in the vicinity of the tailing edge of the impeller and guide vanes rises with <semantics>θ</semantics> increasing, caused by the enhanced wake vortex strength. In addition, the high TEPR area near the inlet of outflow conduit rises with <semantics>θ</semantics> increasing, originated from the improvement of secondary vortices intensity.